2023
DOI: 10.1186/s13045-023-01403-x
|View full text |Cite
|
Sign up to set email alerts
|

GVHD occurrence does not reduce AML relapse following PTCy-based haploidentical transplantation: a study from the ALWP of the EBMT

Abstract: The association between graft-versus-host disease (GVHD) occurrence and acute myeloid leukemia (AML) relapse in patients treated with HLA-haploidentical allogeneic hematopoietic stem cell transplantation (Haplo-HCT) with post-transplant cyclophosphamide (PTCy)-based GVHD prophylaxis has remained debated. Here, we addressed this issue in patients with active AML at transplantation. 2-year cumulative incidences of relapse and leukemia-free survival (LFS) were 49% and 32.3%, respectively. There were no associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Therefore, we treated the development of acute or chronic GVHD at their worst severity as a time-varying covariate. A recent registry study has demonstrated that grade I acute GVHD was associated with better survival but this was not the case for grade II acute GVHD in patients with AML after PTCy-haplo transplantation 43 . The impact of grade I and grade II acute GVHD should be investigated separately in the future studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, we treated the development of acute or chronic GVHD at their worst severity as a time-varying covariate. A recent registry study has demonstrated that grade I acute GVHD was associated with better survival but this was not the case for grade II acute GVHD in patients with AML after PTCy-haplo transplantation 43 . The impact of grade I and grade II acute GVHD should be investigated separately in the future studies.…”
Section: Discussionmentioning
confidence: 97%
“…Fourth, information on minimal residual disease (MRD) was not available in this study. Previous studies suggested a different impact of acute GVHD on survival between AML patients in complete response (CR) and not in CR 37 , 43 . Finally, it has been suggested that immunotherapy approaches can enhance GVM effects without exacerbating GVHD 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients who developed maximum-severity grade II aGVHD, compared with those who did not, were shown to have a significantly lower relapse rate following HLA-matched allo-HCT using PTCy, suggesting that both GVHD-dependent and -independent GVT effects may exist in PTCy based allo-HCT ( 14 , 15 ) and it is possible that PTCy cannot effectively separate harmful alloreactive reactions and the beneficial GVT effect since GVHD can contribute to the GVT effect. By contrast, an important finding is that a large population analysis of the European Society for Blood and Marrow Transplantation (EBMT) registry data of patients with acute myeloid leukemia (AML) undergoing PTCy-haplo did not show that grade II acute GVHD was associated with relapse incidence ( 16 ); therefore, it was not determined whether the development of GVHD contributed to the GVT effect in PTCy-based allo-HCT.…”
Section: Introductionmentioning
confidence: 99%